Web-Based Inventory Information System at PT. Tunas Tasik - Kurnia, Okto; Muchammad Wahabi; Daldiri, Daldiri (KH. A. Wahab Hasbullah University, 2024)
The complexity of the company, driven by changes in the very dynamic environment, needs to be supported by a new design for the processing of stock data at PT. Tunas Tasik is still done manually, so efforts are being made to implement a special application system for the management of goods data; therefore, a responsive web-based information system is needed that can speed up the process of managing goods data. The methods used in this study are observation and interview methods. From the results of the analysis of the web-based goods data management application, which will be described using UML (Unified Modelling Language) notation, Activity Diagram and ERD, to be further implemented using the PHP programming language and database using MySQL. so that it can further improve work effectiveness and provide information quickly and accurately.